Geometria Projetiva no ensino do espaço tridimensional e na estrutura de jogo de Dobble - Pavaneli, Maicon Donizetti Dias (Universidade Federal de São Carlos, 2019)
Projective Geometry gives us the means to demonstrate and discover properties of ﬁgures, it is a possibility to understand mathematically the study of the descriptive properties of geometric ﬁgures. And after Poncelet oﬀering his own means to demonstrate and discover properties of ﬁgures having thus the end of the intuitive “age” of Projective Geometry. We study in this work the basic fundamentals of the projective geometry, its representation and manipulation. We used a didactic sequence based on didactic engineering, ﬁrst investigating and ﬁnally a posteriori analysis. Activities will be presented where students will learn some techniques for better spatial representation using Geogebra. In the end a game is presented, called Dobble’s game, in which we made an exposition of mathematical concepts that involve the structure of the game.
Projective Geometry in the teaching of three-dimensional space and the game structure of Dobble
Keywords: Geometria projetiva; Geometry, Projective; CIENCIAS EXATAS E DA TERRA::MATEMATICA